Ligand-free synthesis of gold nanoparticles incorporated within cylindrical block copolymer films. Issue 30 (20th July 2018) - Aubrit, Florian; Testard, Fabienne; Paquirissamy, Aurélie; Gobeaux, Frédéric; Wang, Xuan; Nallet, Frédéric; Fontaine, Philippe; Ponsinet, Virginie; Guenoun, Patrick
Abstract : Sonochemically produced gold nanoparticles are organized into oriented block copolymer cylinders to obtain anisotropic plasmonic nanocomposite films. Abstract : We report a method to incorporate non-functionalized gold nanoparticles (AuNPs) in oriented cylindrical phases of poly(styrene)- b -poly(vinylpyridine) (PS- b -PVP) block copolymers, perpendicular or parallel to a substrate. The combination of AFM, TEM, GISAXS and spectroscopy allows complete characterization of the nanocomposites. AuNPs are produced by the ultra-sound reduction of a gold salt in the copolymer solution, prior to the deposition of the films by spin-coating. The AuNPs are found to be located within the PVP cylinders exclusively. Sizes from 2 to 4 nm are tuned as a function of the initial gold salt concentration. The seeded-growth of these pre-formed AuNPs was also achieved by a further ultra-sound treatment to produce larger AuNPs (up to d = 10 nm) with plasmon resonance properties. For parallel cylinders, the presence of AuNPs in the PVP domains disturbs the organization, while for perpendicular cylinders, the PVP domains are swollen without any change in their orientation. The synthesis of AuNPs inside the copolymer was also performed by radiolysis, through irradiation of the copolymer solution or the copolymer film, both containing the gold salt. In these cases, the presence of plasmonic AuNPs was also evidenced. Offering a control of the AuNP size (<2 nm to 10 nm) and location, the presented method is a promising way to insert plasmonic AuNPs into oriented cylinders for achieving anisotropic geometries of valuable interest for optics.